Greenhouse gas (GHG) emissions and priority action in climate mitigation in the agriculture sector - Costa, Ciniro (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
This presentation was given by Ciniro Costa Jr. (CCAFS) at a Rabobank Climate Change Training Session on March 3, 2021.